2017
DOI: 10.1093/annonc/mdx488
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations and radioresistance in breast cancer: an analysis of the ProfiLER protocol

Abstract: PIK3CA mutation was associated with a lower risk of local relapse in this population of BCs. This is consistent with recent studies suggesting PIK3CA to be part of biological pathways impacting the radiosensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The development of a radiation-resistant tumor cell population may be partly responsible for the disease recurrence experienced by 10-15% of patients with BC after breast-conserving strategy [14]. Therefore, improving radiosensitivity in BC FITC/PI, fluorescein isothiocyanate/propidium iodide; miR-93-5p inhibitor, hsa-miR-93-5p inhibitor; IR, ionizing radiation; miR-93-5p, hsa-miR-93-5p mimics; SD, standard deviation enhances the radiosensitivity of BC cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…The development of a radiation-resistant tumor cell population may be partly responsible for the disease recurrence experienced by 10-15% of patients with BC after breast-conserving strategy [14]. Therefore, improving radiosensitivity in BC FITC/PI, fluorescein isothiocyanate/propidium iodide; miR-93-5p inhibitor, hsa-miR-93-5p inhibitor; IR, ionizing radiation; miR-93-5p, hsa-miR-93-5p mimics; SD, standard deviation enhances the radiosensitivity of BC cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of PIK3CA mutations in breast cancer remains complicated and controversial in literatures. Sobhani et al suggested that mutated PIK3CA represents an independent negative prognostic factor in breast cancer 48 ; while several studies indicated that mutations in PIK3CA were associated with favorable prognostic factor in unsorted breast cancer 49 52 . Notably, the detailed stratification of molecular subtypes in recent years has helped reduce controversy on the topic.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported an increase in expression of genes involved in epithelial-to-mesenchymal (EMT) transition, angiogenesis, and proliferation in a highly radio-resistant tumor, glioblastoma [11]. Also, a study of genomic alterations in breast cancer patients revealed an association of phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) mutation with loco-regional recurrence in case of breast cancer [12]. Thus, identification of specific radio-resistance-associated signature patterns can be of immense utility to develop novel treatment strategies or introduce "customized" radio-sensitizers to prevent recurrence [13].…”
Section: Introductionmentioning
confidence: 99%